VVV-WIT-01: highly obscured classical nova or protostellar collision? - Lucas, Philip; Minniti, D.; Kamble, A.; Kaplan, D. L.; Cross, N.; Dékány, István; Ivanov, V. D.; Kurtev, R.; Saito, R. K.; Smith, L. C.; Catelan, M.; Masetti, N.; et al. (Monthly notices of the Royal Astronomical Society, 2020)
ABSTRACT. A search of the first Data Release of the VISTA Variables in the Via Lactea (VVV) Survey discovered the exceptionally red transient VVV-WIT-01 (H − K